Terahertz emission using quantum cascade laser - Teo, Jason Chin Sen. (2009)
This report serves to highlight what has been accomplished in this project for the academic year 08/09. The scope of the project is to study how quantum cascade laser work and design it to emit terahertz frequency. This report covers the theoretical models and calculations of the band structures and related parameters. The eight-band k.p models combined with an envelop function approximation have been used. Various quantum well types, including single quantum well, double-barrier quantum well, and coupled quantum well have been studied. The calculated intersubband transition energy is in agreement with results that was published. In addition, the enlighten InGaAsN well combined with AlAs barrier also motivates us to design GaAs based quantum cascade laser (QCL) structures emitting within 3-5 μm range. Consequently, an optimized structure is obtained with 3.4 μm emission under electric field, which is very useful for the design of mid-infrared wavelength QCLs by the matured GaAs technology.